The Goal of Classroom Instruction: Entertainment or Learning - Don B. Croft (Educational Considerations, 1974)
Using nearly 10,000 college students, this study isolated six factors of an instructor's behavior which influence how much students learn and whether they would take another course from the instructor. The results provide suggestions for improving your instruction.